Letter - Southampton Trades Council & Labour Representation Committee, 7 May 1926 (Southampton)
1926-05-07 "Letter - Southampton Trades Council & Labour Representation Committee, 7 May 1926" [g0312001.jpg], 7 May 1926 Local Organisation